Communication strategies in the names and descriptions of pop culture podcasts - Różalska, Marianna (Linguistic creativity in marketing, 2022)
The aim of the article is to identify communication strategies in podcast marketing communication - a new form of distribution of promotional, informational and educational content. Taking the perspective of a constructivist communication theory, 116 podcasts excerpted from Spotify were analyzed. The author explored only the names and descriptions of podcasts from three categories: music, games, and arts and entertainment, as representing the subject of pop culture. Then, a qualitative description of the five most commonly used communication strategies was made: creating an authority, pointing to distinguishing features, relational-based, humor and irony, imitation of the recipient's language. Mechanisms, concepts and other communication measures that create strategies were taken into account. Research results show a tendency towards narrativity, community and building relationships. They indicate the specificity of the communication mechanisms used in the podcast sector. This content, easy to receive and attracting more and more enthusiasts, has enormous marketing potential. However, it is to a small extent oriented towards persuasiveness.